In and Out of Suriname - Carlin, E.B (Caribbean Series, 2015)
This title is available online in its entirety in Open Access In and Out of Suriname: Language, Mobility and Identity offers a fresh multidisciplinary approach to multilingual Surinamese society, that breaks through the notion of bounded ethnicity enshrined in historical and ethnographic literature on Suriname.